Workplace Flexibility Practices and Corporate Performance: Evidence from the British Private Sector. (12th March 2014) - Whyman, Philip B.; Baimbridge, Mark J.; Buraimo, Babatunde A.; Petrescu, Alina I.
<x xml:space="preserve">Abstract</x> This paper investigates the relationship between workplace flexibility practices (WFPs) and corporate performance using data from the British Workplace Employment Relations Survey 2004. Disaggregating WFPs into numerical, functional and cost aspects enables the analysis of their relationships to an objective measure of corporate performance, namely workplace financial turnover. Furthermore separate analyses are presented for different types of workplace: differentiated by workforce size; ownership; age; wage level; and unionization. Results show that different types of workplaces need to pay attention to the mix of WFPs they adopt. We find that certain cost WFPs (profit‐related pay, merit pay and payment‐by‐results) have strong positive relationships with corporate performance. However, training delivers mixed corporate performance results, while the extent of job autonomy and the proportion of part‐time employees in a workplace have an inverse association with corporate performance. Given the limited existing research examining disaggregated measures of WFPs and objectively measured corporate performance, this paper offers useful insights for firms, policy makers and the overall economy.